2013
DOI: 10.1177/000313481307900427
|View full text |Cite
|
Sign up to set email alerts
|

Less Common Nontraumatic Bowel Perforations: Diagnosis and Management through a Retrospective Study

Abstract: Nontraumatic bowel perforation has always been a consideration because of associated morbidity and mortality. The aim of this study is to define etiologies, treatment, and outcomes as well as to highlight difficulties in the diagnosis and management of nontraumatic bowel perforation. We conducted a retrospective study of 35 patients with less common nontraumatic bowel perforations hospitalized during a six-year period. The most common cause was ulcerative colitis (34.3%). Abdominal pain was the constant sympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Early diagnosis before patients' conditions deteriorate, will decrease mortality and morbidity rates. 16 Small bowel perforation is associated with fewer complications when it is treated earlier than 24 h after injury. Delay in surgical treatment beyond this deadline will not significantly increase the mortality, although the complication rate will be dramatically higher.…”
Section: Discussionmentioning
confidence: 99%
“…Early diagnosis before patients' conditions deteriorate, will decrease mortality and morbidity rates. 16 Small bowel perforation is associated with fewer complications when it is treated earlier than 24 h after injury. Delay in surgical treatment beyond this deadline will not significantly increase the mortality, although the complication rate will be dramatically higher.…”
Section: Discussionmentioning
confidence: 99%
“…Among the other histomorphological findings of BD, near-normal mucosa is observed in regions away from the lesions, and lymphoid aggregates or granulomas are not found [ 8 , 15 ]. In general, mortality of colonic perforation ranges from 35% to 47% [ 19 ]. Kasahara et al [ 17 ] reported that postoperative ulcer recurrence within 6 months occurred in 22 of 34 patients (65%), whereas recurrence did not occur in 5 patients after more than 3 years of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Crohn’s disease has been reported in the literature to present with symptoms similar to ruptured appendicitis [1] , military tuberculosis [2] , and even condylomata acuminata [3] . Crohn’s disease is primarily diagnosed in children in the context of nontraumatic bowel perforations [4] . Very rarely is it first diagnosed in the context of trauma.…”
Section: Introductionmentioning
confidence: 99%